Proposta de aplicação de ferramentas gerenciais de controle de estoque para a tomada de decisão em um supermercado - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Due to the significant increasing of market competitiveness, increases the importance an inventory management based on data and facts and with it, is vital the use of management tools to support control, planning and decision making in various sectors of business. This study aimed to demonstrate the importance of using management tools applied in inventory control in a supermarket in the city of Aceguá, Rio Grande do Sul. In this study was carried out a bibliographic reference, which was faced with the reality of management inventory currently applied in the supermarket, from the execution of an exploratory research through semi-structured interviews, documental verification, observation and analysis of controls, systematic and inventory tools existing in the company. This work is featured as a case study, where a quantitative research will be performed. From the results obtained were proposed actions to set the current standard of the company's inventory management and then identify if the model is effective, and finally, proposals are designed to implement improvements in this model.
Keywords: Engenharia; Engenharia de produção; Controle de estoque; Sistemas de gestão; Cooperativa agrícola; Cooperativa; Previsão de demanda; CNPQ::ENGENHARIAS